Antiinflamatory and antidepressive activities of Extract Curcuma xanthorrhiza Roxb in Systemic Lupus Erythematosus - Maria Caecilia Setiawati; Zulies Ikawati; I Nyoman Kertia (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Systemic Lupus Erythemathosus is an autoimmune, inflammatory, chronic disorder characterized by multiorgan system involvement. Depression and anxiety are frequent complaints among patients with lupus erythematosus, so antidepressive treatment should be an important element of the therapy of patients with lupus erythematosus. Research into curcumin’s potential as a treatment for depression is still in its infancy, although several potential antidepressant mechanisms of action have been identified. 4-weeks double-blind, placebo-controlled clinical trial was conducted in 14 SLE patients (10 as treatment group and 4 as control group) The BDI (Beck Depression Inventory) score was calculated and TNF α concentration was measured in the serum subjects before and after treatment. Correlation between TNF α concentration and BDI was assessed. After 4 weeks treatment, the TNF α concentration from subjects in treatment group were significantly lower than before ( p <0.001) but the BDI score were not significantly lower than before (p = 0.059). The TNF α concentration and BDI score showed positive correlation, p = 0,024. This study demonstrate that Curcuma xanthorrhiza Roxb extract can decrease serum TNF α concentration and reduce clinically symptoms of depression in SLE patients